Teaching home safety skills to children with autism spectrum disorders - Mortaş Kum, Ayşe; Bilmez, Hatice (Frontiers in Psychiatry, 2025)
Children diagnosed with autism spectrum disorder (ASD) are 2 to 3 times more likely to experience injury or abuse than their typically developing peers of the same age. Parents have limited knowledge about the home safety skills of children with autism and often do not know how to respond in risky situations. In addition, fathers are generally less involved in the educational processes of children with ASD compared to mothers. The purpose of this study was to evaluate the effectiveness of the video modelling presented by fathers in teaching home safety skills (avoiding chemicals) to children with ASD. This study designed a single-subject multiple probe design with probe phases across four preschool-aged children with ASD (ages 3–4) and their fathers. Results demonstrated that all children acquired, generalized, and maintained the targeted safety skill with 100% success after six instructional sessions. Social validity findings indicated positive perceptions from fathers.